The impact of cold application on pain and comfort during the process of diabetic foot care - Turan, Mensure; Ozbay, Hediye; Avsar, Melek (Elsevier Ireland Ltd, 2025)
Background and Aim: Given the significance of pain management in the context of diabetic foot ulcer (DFU) care, particularly in terms of ensuring patient adherence to treatment regimens, this study was undertaken to ascertain the impact of cold washing on pain and comfort levels during diabetic foot care. Methods: A single-blind randomized controlled trial was conducted in the chronic wound care clinic of a teaching and research hospital in the southeastern region of Turkey. The sample consisted of 68 patients, with 34 assigned to the cold application group and 34 assigned to the control group. Pain and comfort levels were recorded at baseline, and during and after the application of a 0.9% NaCl solution (cold or warm) during DFU care. Results: A comparison of the Cold Application group with the control group revealed a statistically significant reduction in post-intervention pain scores (p = 0.000) and a statistically significant increase in comfort scores (p = 0.000) over time. Conclusion: It can be posited that cold washing represents an efficacious intervention in the management of pain and discomfort associated with diabetic foot care.
Keywords: Diabetic foot; Pain; Cold application; Comfort